Tinjauan Ketimpangan Distribusi Pendapatan dalam Perspektif Ekonomi Klasik dan Islam Pada Ekonomi Modern - Muhammad Taufiq; Maria Melidiana; Jaya Eka Sasmita; Lu'luul Bintani; Agung karunia; Anas Malik; Nabila Putri Delvi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Income distribution inequality is a structural problem that is widely discussed in classical, Islamic, and modern economics. This study discusses how these three approaches understand the roots of inequality and the solutions offered to create distributional justice. Inequality not only affects the economic sector, but also increases social disparities and disrupts community cohesion. Therefore, theoretical comparisons are important. This study analyzes classical economic views based on market mechanisms, explores the principles of distribution in Islamic economics that emphasize spiritual values and social responsibility, and examines modern economic responses to inequality through fiscal policy and the role of the state. The research was conducted using a qualitative method based on a literature review. The results show that the three approaches have different contributions: market efficiency in classical economics, sharia justice in Islamic economics, and a combination of markets and public policy in modern economics. The integrative approach is considered more relevant.